Effects of local Infiltration of Bupivacaine in total hip and knee replacement for post - operative analgesia - Al-Shamari, Ahmed L. (AL-Kindy College Medical Journal, 2015)
Background: Pain is one of the most postoperative complications of surgical wound especially within first 24 hrs. leading to delay hospital discharge, stress gastritis and increasing blood pressure. As wound infiltration with long acting local anesthetic (bupivacaine) has been proved to be effective after orthopedic surgeries especially total hip and knee replacements.Objective: our study was designed to determine theeffectiveness of local infiltration of 0.5% of bupivacainebefore closure of surgical wounds in controllingpostoperative pain and improve patient’s outcome after totalhip and knee replacement surgeries in first 24hrspostoperative period.Methods: Twenty patients from class I (healthy patients) and class II (patients mild systemic diseases) of ASA (American society of anesthetists) undergoing elective orthopaedic surgeries were randomly assigned in two groups and (both of them have general anesthesia); Group A (10patients) received local infiltration of 0.5% bupivacaine before closure of surgical wounds and group B (10 patients) received local infiltration of 0.9% of normal saline. We use uniform technique of anesthesia in both at rest and on passive mobilization by nurses and residents groups. Visual analogue pain scale scores were assessedblinded to analgesic treatment and we check the needs for analgesic drugs post-operative in both groups.Results: Group A showed a significant reduction inpostoperative pain at rest and on mobilization afterinfiltration of 0.5% bupivacaine with short hospital stay andonly 3 patients need for post-operative analgesia ,while allpatients in group B require at least single dose of analgesialike pethidine or non-steroidal anti-inflammatory drugs.Conclusion: The use of 0.5% Bupivacaine by wound infiltration is effective for post-operative pain relief, as it reduces the requirements for additional post-operative analgesia after total hip and knee replacements.